The Influence of Problem Solving Method on Student Learning Outcomes in Science Subjects at SMP Negeri 1 Momunu, Buol Regency: Pengaruh Metode Problem Solving Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPA di SMP Negeri 1 Momunu Kabupaten Buol - Trianto, Manap; Putri, Regina Triana; Masrianih, Masrianih (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2025)
The purpose of this study is to characterize how the Problem Solving Learning approach affects science students' learning outcomes at SMP Negeri 1 Momunu. By dividing research subjects into two groups—an experimental group and a control group—this kind of study is known as a quasi-experiment (Quasy Experiment). The Nonequivalent Control Groups Design was the study design that was applied. All members of class VIII made up the study's population. Purposive sampling was the sample strategy employed, and a multiple-choice written test was utilized as the study instrument. Class VIII A and class VIII B are the research samples. Primary data from the completion of the pretest and posttest constitute the type of data used in the study. This study's data analysis method makes use of testing for hypotheses (t test). The average posttest results for the experimental class and control class were, respectively, 80.22 and 74.77 in the experimental class. The research data analysis results show that there is an influence of the Problem Solving learning method on student learning outcomes in science subjects at SMPN 1 Momunu. The t test, with assistance from the SPSS version 29 application, yielded a Sig value (two-sided p) of 0.034 < 0.05, meaning that Ha is accepted and Ho is rejected.